2018
DOI: 10.1039/c8nr02832j
|View full text |Cite
|
Sign up to set email alerts
|

Formation of porous Cu hydroxy double salt nanoflowers derived from metal–organic frameworks with efficient peroxidase-like activity for label-free detection of glucose

Abstract: Currently, nanomaterials with peroxidase activity have become an important colorimetric tool for biomolecular detection. However, compared with natural enzymes, the efficiency of most nanozymes is still lower. Here, with a leaf-like metal-organic-framework-5 as both a precursor and a template and copper acetate as a second precursor, hierarchical Cu hydroxy double salt (HDS) nanoflowers have been prepared and used as a label-free glucose colorimetric detection platform. We have demonstrated a scalable and faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Figure 2 showed the FT-IR spectra of Ls and Cu/Ls MOF. The spectrum of the Ls featured a characteristic peak at 1616 cm − 1 , due to the asymmetric stretching vibration of the carboxylate moiety, along with symmetric stretching vibrations at 1402 cm − 1 (Li et al, 2018). The splitting of the broad C = O asymmetric stretching vibration band at peaks 1616 cm − 1 re ected the formation of Cu-O coordination (1598 and 1660 cm − 1 ) (Liang et al, 2017;Shams et al, 2019).…”
Section: Structural Characterization Of Cu/ls Mofmentioning
confidence: 99%
“…Figure 2 showed the FT-IR spectra of Ls and Cu/Ls MOF. The spectrum of the Ls featured a characteristic peak at 1616 cm − 1 , due to the asymmetric stretching vibration of the carboxylate moiety, along with symmetric stretching vibrations at 1402 cm − 1 (Li et al, 2018). The splitting of the broad C = O asymmetric stretching vibration band at peaks 1616 cm − 1 re ected the formation of Cu-O coordination (1598 and 1660 cm − 1 ) (Liang et al, 2017;Shams et al, 2019).…”
Section: Structural Characterization Of Cu/ls Mofmentioning
confidence: 99%
“…Compared with peroxidases and other nanoparticles, CNPs are low-cost, easily accessible, and stable. 32,33 Structural analyses of CNPs revealed that they possessed a nanocrystalline core of graphitic sp 2 carbon atoms, functionalized with peripheral hydroxy and carboxylic/carbonyl moieties. 34 Functionalization of graphene surfaces with carboxylic groups is vital for the reduction of H 2 O 2 according to density functional theory.…”
Section: Optimization Of Experimental Conditionsmentioning
confidence: 99%
“…Afterward, a variety of nanomaterials including metal oxides (ZnFe 2 O 4 , V 2 O 5 ), metal sulfides (MoS 2 , CuS), noble metals (Au, Ag, Pd), quaternary CuZnFeS nanocrystals, graphene oxide, metal–organic framework (MOFs), , iron doped CuSn­(OH) 6 microspheres, ternary polyaniline–MnO 2 –Pd nanowires, and nitrogen-doped carbon nanomaterials were discovered that had peroxidase-like activity in association with H 2 O 2 . The important characteristics of these enzyme-mimetic nanomaterials were found to detect H 2 O 2 , glucose, immunoassay, glutathione, and cancer cell detection . However, one of the major limitations of these nanomaterials is their synthesis from doping of chemical materials and the use of expensive and toxic chemicals; this, along with multistep synthesis, made it a tedious process which limits the application of these nanomaterials .…”
Section: Introductionmentioning
confidence: 99%